Исторические этапы развития социально-экономической и экологической политики Каракалпакстана в годы независимости (1991-2021гг.) (SCIENCE and SOCIETY, 2024)
The article discusses issues of research into the historical stages of development of the analysis carried out on the development of stages of environmental policy, socio-economic and environmental policy of Karakalpakstan during the years of independence (1991-2021).